PENGARUH TOTAL ASSET TURNOVER, FIRM SIZE DAN CURRENT RATIO TERHADAP PERTUMBUHAN LABA PADA PT.SIRMA PRATAMA NUSA - Sanchez Sinaga, Monica; Simanullang, Agnes Emma; Yanti, Ira; Luck Amelia S, Jholant Bringg (EDUTECH CONSULTANT, 2019)
This study aims to examine and analyze the influence of total asset turnover, firm size and current ratio on profit growth in PT.Sirma Pratama Nusa period 2014-2017. The research approach used in this study is an associative quantitative approach with causal character. Population of this study in PT.Sirma Pratama Nusantara is financial statements in PT.Sirma Pratama Nusantara. From the population in PT.Sirma Pratama Nusantara has chosen with saturated sampling method. In this study the analytical technique used was multiple linear regression analysis with test F and test t. Based on the results of partially shows that total asset turnover effect and not significant, while the firm size has a significant effect and current ratio negative effect and significant on profit growth. Based on the results of simultaneous shows that total asset turnover, firm size and current ratio have an effect and significant on profit growth.